A sensorless control scheme based on fractional order super-twisting algorithm and improved FLL for PMSM - Liqun Huangfu; Cen Chen; Tao Zhang (Advances in Mechanical Engineering)
To further improve the accuracy of sensorless control at medium and high speeds for permanent magnet synchronous motor (PMSM) and expand its applicability, this paper proposes a new scheme that uses a sliding mode observer and a frequency-locked loop (FLL) for control. The combination of the super-twisting algorithm (STA) and fractional calculus algorithm (FCA) is applied to the observer, which improves the convergence speed and accuracy. In response to the limitations of phase-locked loops (PLLs), a second-order generalized integral frequency-locked loop (SOGI-FLL) is introduced into the control system to be compounded to form a novel control system with compensation, which filters the signal while achieving accurate tracking of rotor position information. Finally, a series of experiments were conducted to compare the performance of the proposed control scheme with conventional control schemes. The superiority and feasibility of the sensorless control scheme were verified through experimental results on a permanent magnet synchronous motor platform.